Membentuk Self Concept Positif pada Anak (Pendekatan Parenting Skill) - Sriyanti, Lilik (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2009)
Individual concept is one’s view of oneself as something invaluable or worthless. The view of the self will influence to accomplish efforts, the motivations to achieve the ideals, and behaviors. The positive self-concept elicits the appearance of self-esteem and the spirit to move forwards. The individual positive concept tends to view others from positive thinking and vice versa. Individual concept is formed through learning and environmental influence particularly parents. The change of individual concept may be influenced by personal stipulation, failure, and depression – even though this can be controlled through appropriate rearing. Parenting is very influential to the creation of individual concept of the children. Unfortunately, parents and teachers do not realize that their attitude and conduct have broken down the children’s self-esteem. This automatically creates the negative individual concept of them. This is the time to change to the scientific parenting model and affection. The model does not only emphasize parents’ ego but also appreciating children as growing and developing individual, as well as learning individual with their strengths and weaknesses.